2015
DOI: 10.1093/tropej/fmv027
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Frozen Plasma Use in a Neonatal Unit in South Africa

Abstract: FFP was often used in accordance with published guidelines in our neonatal unit. However, the appropriate use and effectiveness of FFP in improving neonatal outcomes undermines the rationale for FFP usage in current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Within the cesarean section–only studies, placenta previa at 27% (47 of 431) and obstructed labor at 25% (44 of 431) were the leading indications for transfusion. Among newborn babies, WB and RBC products were used in relatively equal measure, and neonatal jaundice and bleeding together accounted for 66% (218 of 477) of the products transfused overall …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the cesarean section–only studies, placenta previa at 27% (47 of 431) and obstructed labor at 25% (44 of 431) were the leading indications for transfusion. Among newborn babies, WB and RBC products were used in relatively equal measure, and neonatal jaundice and bleeding together accounted for 66% (218 of 477) of the products transfused overall …”
Section: Resultsmentioning
confidence: 99%
“…These 10 studies were used for the primary outcome calculation. The rest of the studies evaluated blood use among specific patient groups: nine studies among pediatric patients only; five on obstetrics and gynecology patients; three among cesarean section deliveries; three among newborn babies; two among elective surgical operations; two exclusively on the use of platelets; two on the use of autologous blood; and one among hepatogastroenterology patients . Most studies made a clear distinction between the number of patients transfused and the number of blood products used for transfusion.…”
Section: Resultsmentioning
confidence: 99%
“…We compare FFP concentration to clotting factors reported in France and the literature. FFP is a labile blood product with numerous and varied indications in current medical practice [12,13,15,16]. In developing countries in Africa, FFP remains the only source of clotting factors available for the management of hemorrhagic diseases such as hemophilia and other bleeding diseases [1,16].…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the cause, management of bleeding is a life-threatening emergency. Treatment includes administration of concentrates for specific clotting factor, hemostatic drugs such as ethamsylate (which increase capillary endothelial resistance and promote platelet adhesion), antifibrinolytic drugs (tranexamic acid) and fresh frozen plasma (FFP) [12][13][14]. Considering, its composition, FFP appears to be an efficient alternative to manage hemorrhagic episodes in hemophilic patients or in other coagulation proteins deficiency such as fibrinogen as no specific concentrate is available.…”
Section: Introductionmentioning
confidence: 99%
“…Summary of Evidence The summary of findings given in Table 14 includes 7 critical or important outcomes and the effect size with 95% CI for the intervention and the control. These have been obtained from 4 observational studies 5,6,77,78 providing overall a very low quality of evidence for the recommendation. Studies have shown a correction of deranged PT, APTT, and serum fibrinogen levels following FFP transfusion prior to surgery or invasive procedure in neonates with deranged coagulation profile.…”
Section: Practice Question 12: Should Fresh Frozen Plasma Transfusionmentioning
confidence: 99%